Etiology, Clinical Picture, Diagnosis and Treatment Methods of Cephalohematomas in Newborns (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In the department of neurosurgery of the multidisciplinary clinic of Samarkand State Medical University, 60 babies treated with cephalohematoma disease, clinical course, diagnostic and treatment features were studied. Occurrence of cephalohematomas can be caused by extragenital diseases of a pregnant mother, stress during childbirth, continuous exertion, use of vacuum extractor, caesarean section. Clinical and neurological examinations did not reveal general brain and focal symptoms in infants, neurosonography, craniography and multispiral computer tomography of the brain were used to diagnose them. For the purpose of treatment, the liquefied hematoma under the periosteum was evacuated with the help of a medical syringe, and the thickened hematoma was cut through the skin, and in ossified cases, the ossified layer of the cephalohematoma was cut and removed using bone scissors.